2018
DOI: 10.1007/s00384-018-3030-x
|View full text |Cite
|
Sign up to set email alerts
|

Robotic rectal cancer surgery in obese patients may lead to better short-term outcomes when compared to laparoscopy: a comparative propensity scored match study

Abstract: PurposeLaparoscopic rectal surgery in obese patients is technically challenging. The technological advantages of robotic instruments can help overcome some of those challenges, but whether this translates to superior short-term outcomes is largely unknown. The aim of this study is to compare the short-term surgical outcomes of obese (BMI ≥ 30) robotic and laparoscopic rectal cancer surgery patients.MethodsAll consecutive obese patients receiving laparoscopic and robotic rectal cancer resection surgery from thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 55 publications
1
20
0
1
Order By: Relevance
“…The use of da Vinci robot has spread rapidly in colorectal cancer surgery even if its alleged reported advantages over the direct manual laparoscopic approach, including lower conversion rate, shorter p-gcurve and improved functional outcomes (1,3,(6)(7)(8)18], have not been fully confirmed by the recently published randomized clinical trial, and meta-analyses [9][10][11][12]. The results of these studies indicate that selected patients, such as obese, men, those with cancer of the lower rectum, and patients operated after receiving preoperative chemoradiotherapy, are those for whom there is high-level evidence of superiority of RAS over direct manual laparoscopic surgery [25][26][27][28][29][30]. However, the downside of the RAS technique, which remains a critical issue preventing its widespread uptake, relates to its high capital, amortization, recurrent costs and longer operating time.…”
Section: Discussionmentioning
confidence: 99%
“…The use of da Vinci robot has spread rapidly in colorectal cancer surgery even if its alleged reported advantages over the direct manual laparoscopic approach, including lower conversion rate, shorter p-gcurve and improved functional outcomes (1,3,(6)(7)(8)18], have not been fully confirmed by the recently published randomized clinical trial, and meta-analyses [9][10][11][12]. The results of these studies indicate that selected patients, such as obese, men, those with cancer of the lower rectum, and patients operated after receiving preoperative chemoradiotherapy, are those for whom there is high-level evidence of superiority of RAS over direct manual laparoscopic surgery [25][26][27][28][29][30]. However, the downside of the RAS technique, which remains a critical issue preventing its widespread uptake, relates to its high capital, amortization, recurrent costs and longer operating time.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review showed that laparoscopic surgery for rectal cancer in obese patients is technically challenging because of the longer operative times, higher risk of postoperative complications, and higher rates of conversion to OS compared with non‐obese patients . Recent retrospective case‐control studies that compared obese versus non‐obese patients (body mass index of ≥30 vs <30 kg/m 2 , respectively) undergoing robotic colorectal surgery consistently showed no difference in the conversion rate, rate of CRM, intraoperative or postoperative complications, or length of hospital stay . Shiomi et al .…”
Section: Short‐term Outcomesmentioning
confidence: 99%
“…This observation can confirm that the LOS is not relevant to the observed increase in total costs following RRS. Considering obese patients, RRS led to a significantly shorter LOS, and lower 30-day readmission rate although it the operative time was longer with higher intraoperative costs when compared to LRS [34,35]. The overall oncological outcomes [36] and postoperative quality of life [37] were not different in the patients after undergoing LRS and RRS.…”
Section: Methodsmentioning
confidence: 99%